Conducting polyanilline based paints on hot dip galvanized low carbon steel for corrosion protection - Deshpande, P.; Vagge, S.; Jagtap, Sharmili; Khiarnar, R.; Kelkar, Sarika A.; More, Minal (Bulgarian Chemical Communications, 2012)
Conducting polyaniline based paints have been applied on hot dip galvanized low carbon steel samples. The corrosion protection performance of these paint coatings was evaluated by using Tafel plots and impedance spectroscopy. It was found that the paint coatings offered significant corrosion protection to hot dip galvanized low carbon steel in aqueous 3.5 wt % NaCl solution.
Keywords: Conducting polyaniline based paints; corrosion prevention; hot dip galvanized low carbon steel

Characterization of the structures and dynamics of phosphoric acid doped benzimidazole mixtures: a molecular dynamics study - More, Minal; Pahari, Swagata; Roy, Sudip; Venkatnathan, Arun (Journal of Molecular Modeling, 2013)
Benzimidazole-based polymer membranes like poly(2,5-benzimidazole) (ABPBI) doped with phosphoric acid (PA) are electrolytes that exhibit high proton conductivity in fuel cells at elevated temperatures. The benzimidazole (BI) moiety is an important constituent of these membranes, so the present work was performed in order to achieve a molecular understanding of the BI-PA interactions in the presence of varying levels of the PA dopant, using classical molecular dynamics (MD) simulations. The various hydrogen-bonding interactions, as characterized based on structural properties and hydrogen-bond lifetime calculations, show that both BI and PA molecules exhibit dual proton-acceptor/donor functionality. An examination of diffusion coefficients showed that the diffusion of BI decreases with increasing PA uptake, whereas the diffusion of PA slightly increases. The hydrogen-bond lifetime calculations pointed to the existence of competitive hydrogen bonding between various sites in BI and PA.
Keywords: Diffusion coefficient; Hydrogen bond; molecular dynamics; Radial distribution functions